APHTHAE AND ORAL APHTHOSIS - Cristian Constantin Budacu; Gabi Topor; Mădălina Matei (Romanian Society of Oral Rehabilitation, 2020)
Aphthae (aphthous stomatitis) is an elementary lesion of the skin and mucous membranes of unknown origin, which presents itself in the form of a vesicle filled with opalescent fluid, which, by rupture, leaves room to a painful ulceration, which heals without leaving traces. It is surrounded by an erythematous rash; with lesions located predominantly in the oral cavity and a high incidence among the population; these are caused by the use of irritating, toxic substances, avitaminoses, overwork, infectious diseases. Oral aphthae are small ulcers of the oral mucosa inside the cheek, on gums, lips or tongue; it causes discomfort but also difficulty during eating or pain during chewing and ingestion of certain foods. The ulcerations that occur tend to recur if these are not treated timely and correctly. The source of an oral aphthae is infectious, and the condition usually occurs when the body becomes stressed and the defence system weakened. In general, aphthous stomatitis may occur due to the usual flora exacerbation favoured by the dental tartar, by irritations caused by the consumption of alcohol, chemicals, spices, smoking, or poor dental hygiene. Oral aphthae, also called aphthous ulcerations or aphthous stomatitis, are small lesions that develop in the soft tissues of the oral cavity or at the base of the gums. These small ulcerations, lesions or oral aphthae are usually very painful, they are not contagious, but their causes are not fully known. There are situations when oral aphthae may be associated with genital disorders, with skin, ocular, digestive or respiratory manifestations or other general signs, which complement the clinical picture of aphthosis. When oral aphthae occur, attention should be paid to correcting digestive disorders, and to avoiding acidic foods, spices, citrus fruits, milk and milk products. Material and method: The study carried out between 2017-2019 includes a number of 434 cases out of which 236 women (54.37%) and 198 men (45.63%) who were diagnosed with oral aphthae, which are minor, isolated, multiple ulcerations, preceded by a vesicle with clean edges, with the bottom covered by a white-yellowish deposit. Results and Discussion: Oral aphthae are due to a bacterium or virus, although the allergy to a particular type of bacterium found in the oral cavity can trigger them. These can be an allergic reaction to certain foods. Conclusions: Studies show that oral aphthae can be determined by a deficient immune system that uses its own antibodies to destroy the cells of the oral mucosa.